Rare earth elements determination in rocky shore gastropod thais clavigera - Miskon, Mohd Fuad; Faudzi, Fikriah; Rahman, Md. Mokhlesur; Yunus, Kamaruzzaman (International Proceedings of Chemical, Biological and Environmental Engineering (IPCBEE), 2014)
Interspatial and inter-tissue variations of rare earth elements (REEs) in Thais clavigera collected from particular sites along the east coast of Peninsular Malaysia, Malaysia were studied. All REEs yielded significant strong positive correlation (p<0.05, p<0.01) among each element in soft tissue and operculum, with some variations in shell. The typical REEs fractionation patterns normalized to chondrite were remarkably similar indicating a common source of the REEs for the whole east coast region. Identical deviations from this pattern were found for Eu and could be explained by their redox chemistry. The ratio of light to heavy REEs, La/Yb in the T. clavigera of 29.47 are remarkably similar to Terengganu River basin soil of 33.00 and Terengganu River sediment of 27.60. Consistent chondrite-normalized patterns suggested that light REEs and heavy REEs fractionation in coastline marine environment produces more light REEs and less heavy REEs.